PENGEMBANGAN KOMPETENSI PEDAGOGIK GURU MELALUI INTEGRASI MEDIA DIGITAL DALAM PROSES PEMBELAJARAN - Sumiati; Nearly Ika Yulianti; Lilis Kholisoh Nuryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of teachers' pedagogic competencies through the integration of digital media is an important step in improving teachers' competence in optimizing the learning process. This type of research is a literature review (literature review), with stages namely collecting relevant research literature, marking several important terms in the research, conducting an in-depth analysis of the literature that has been obtained by compiling discussions, drawing conclusions based on the results of the analysis. The conclusion of this study is that the use of technology and digital media allows teachers to access various learning resources that are more varied, interactive, and easily adapted to the needs of students. With the use of digital platforms, teachers can improve pedagogical skills, enrich teaching materials, and strengthen their ability to manage the classroom effectively. In addition, digital learning media supports collaboration, communication, and student involvement to the fullest. School principals play a leadership role in the application of technology, utilizing technology as the main tool to transform the teaching and learning process.